Block anode for aluminum electrolytic capacitor and preparation method thereof
By covering dielectric substances on the surface of aluminum powder and using block-integrated molding technology to prepare anode of aluminum electrolytic capacitors, the problems of high cost, high energy consumption and difficult to break through the anode foil preparation process in the prior art are solved, and the capacitance capacity is difficult to break through, thus achieving High dielectric constant and high energy density effects.
Patent Information
- Application Number
- CN202411751945.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
There are problems in the preparation process of existing aluminum electrolytic capacitor anode foils, which are high costs, high energy consumption, environmental pollution and difficult to break through capacitance capacity.
By covering dielectric substances on the surface of aluminum powder, block-type anodes are prepared by using block-integrated molding technology, the anode cutting process is reduced, burrs are avoided, and the dielectric constant is increased.
The capacitance capacity and energy density of the bulk anode are improved, energy consumption and environmental pollution during the manufacturing process are reduced, processes are simplified, and service life is improved.
Smart Images

Figure CN119480458A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum electrolytic capacitors, and more specifically to a block anode for aluminum electrolytic capacitors and a preparation method thereof. Background Art
[0002] Capacitors are classified into ceramic capacitors, film capacitors, aluminum electrolytic capacitors, tantalum electrolytic capacitors, etc., and play important roles in circuit systems such as filtering, rectification, coupling, and bypassing. Aluminum electrolytic capacitors are widely used in consumer electronics, communication equipment, energy, automobiles, and many other fields due to their low price, superior performance, and reliability.
[0003] With the continuous development of the industry, the requirements for the electrostatic capacitance and energy density of aluminum electrolytic capacitors are getting higher and higher. The electrostatic capacitance of aluminum electrolytic capacitors is mainly determined by the anode foil. However, the current method of preparing high-specific capacitance anode foil by electrochemical corrosion is facing a development bottleneck, and it is difficult to make a significant breakthrough in electrostatic capacitance. In the process of electrochemical corrosion, a large amount of electrical energy is consumed, and at the same time, a large amount of acidic waste liquid is also generated. Therefore, the anode foil prepared by electrochemical corrosion technology has disadvantages such as high cost, high energy consumption, and environmental pollution. Compared with the corroded anode foil, the powder sintered stacked foil has a higher specific surface area and electrostatic capacitance per unit area. However, the coated powder stacked sintered foil needs to go through more than ten processes such as foil washing, slurry stirring, coating, drying, degreasing, sintering, anodizing, cutting, forming, aging, etc., with many steps and complex processes. However, the common problem of foil anodes is that during die cutting and segmentation, the exposed fresh aluminum needs to be formed again, which will consume additional energy. The large number of burrs generated by the shear friction between the metal tool and the anode foil will increase the leakage current after the device is assembled, seriously affecting the service life. However, when the powder-pile sintered anode foil is wound, the sintering neck is prone to breakage, resulting in a waste of aluminum powder, which not only greatly reduces the extraction rate but also causes a loss of electrostatic capacitance. Summary of the invention
[0004] In view of the above problems, the present invention provides a block anode for aluminum electrolytic capacitors and a preparation method thereof. The present invention coats the surface of aluminum powder with dielectric material to manufacture a high-dielectric composite aluminum electrolytic capacitor block anode. The block-type integrated molding technology reduces the later anode cutting process, and fundamentally solves the problem of edge burrs caused by shearing friction between metal cutters and anode foil. The introduction of dielectric material increases the dielectric constant of the block anode dielectric layer, solving the low capacity problem of the anode foil of aluminum electrolytic capacitors.
[0005] The first object of the present invention is to provide a method for preparing a bulk anode for an aluminum electrolytic capacitor, comprising the following steps:
[0006] Aluminum powder coated with dielectric material, a binder and a solvent are uniformly mixed to obtain a slurry, and the slurry is dried to remove the solvent in the slurry to obtain a mixed powder; the dielectric constant of the dielectric material is greater than the dielectric constant of aluminum oxide.
[0007] The mixed powder is pressed and shaped to obtain a block, the block is degreased at 50°C to 550°C in an oxygen-containing atmosphere, sintered at 250°C to 670°C in an oxygen-free atmosphere, and after sintering, an energizing treatment is performed to obtain a block anode for an aluminum electrolytic capacitor.
[0008] For example, the degreasing temperature is 50°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0009] The sintering temperature is 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 670°C, etc., but is not limited to the listed values. Other values not listed within the above numerical range are also applicable.
[0010] It should be noted that, since the oxide film on the surface of aluminum powder becomes denser as the temperature rises, the dense oxide film is not conducive to the diffusion of aluminum, thus affecting sintering. Therefore, even if the degreasing temperature is high, sintering will not be achieved.
[0011] In a preferred embodiment of the present invention, the dielectric material is one or more of titanium dioxide, hafnium oxide, tantalum pentoxide, niobium oxide, barium titanate, strontium titanate, barium strontium titanate, lead zirconate titanate and bismuth ferrite.
[0012] In a preferred embodiment of the present invention, the density of the block is 1.2 g / cm 3 ~2.4g / cm 3 For example, the density of a block is 1.2 g / cm 3 , 1.4g / cm 3 , 1.6g / cm 3 , 1.8g / cm 3 , 2.0g / cm 3 , 2.2g / cm 3 , 2.4g / cm 3 The above numerical range is not limited to the above numerical values, and other numerical values not listed are also applicable.
[0013] In a preferred embodiment of the present invention, the thickness of the block is 0.5 mm to 1 cm. For example, the thickness of the block is 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, 5.5 mm, 6 mm, 6.5 mm, 7 mm, 7.5 mm, 8 mm, 8.5 mm, 9 mm, 9.5 mm, 1 cm, etc., but is not limited to the listed values, and other values not listed in the above numerical range are also applicable.
[0014] In a preferred embodiment of the present invention, the slurry is composed of the following components in percentage by mass: 40% to 80% aluminum powder coated with a dielectric substance, 0.1 to 10% binder, and the rest is solvent, which is 100% in total.
[0015] For example, the aluminum powder coated with dielectric material is 40%, 50%, 60%, 70%, 80%, etc., the binder is 0.1%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., and the solvent is 10%, 20%, 30%, 40%, 50%, 59.9%, etc., but it is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0016] In a preferred embodiment of the present invention, the binder is one or more of starch, polyvinyl alcohol, urea, polymethyl methacrylate, methyl methacrylate, polystyrene, polyvinyl chloride, stearic acid, glycerol, polyethylene glycol, paraffin, camphor, menthol, benzoic acid, polyethylene oxide, hydroxypropyl cellulose, acrylic resin, polypropylene carbonate, polyvinyl alcohol, polyvinyl butyral and propylene carbonate.
[0017] In a preferred embodiment of the present invention, the solvent is water, methanol, ethanol, terpineol, acetonitrile, acetone, dimethylformamide, N-methylpyrrolidone, n-butanol or methyl ethyl ketone, and more preferably, the solvent is ethanol.
[0018] In a preferred embodiment of the present invention, the degreasing time is 0.5h to 20h. For example, the degreasing time is 0.5h, 1h, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, etc., but it is not limited to the listed values, and other values not listed in the above numerical range are also applicable. More preferably, the degreasing time is 0.5h to 10h.
[0019] In a preferred embodiment of the present invention, the sintering time is 0.5 to 20 hours. For example, the sintering time is 0.5 hours, 1 hours, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, etc., but it is not limited to the listed values. Other values not listed in the above numerical range are also applicable. The sintering atmosphere is any one or more of a vacuum atmosphere, an argon atmosphere, a nitrogen atmosphere, and a hydrogen atmosphere. More preferably, the sintering time is 0.5 to 10 hours.
[0020] In a preferred embodiment of the present invention, the aluminum powder coated with dielectric material is obtained by vapor deposition, liquid coating or solid mixed coating.
[0021] More preferably, the vapor deposition method is chemical vapor deposition, atomic layer deposition, molecular layer deposition, fluidized bed deposition or magnetron sputtering; the liquid coating method is sol-gel deposition; and the solid mixed coating method is dry mixing or wet mixing of aluminum powder and dielectric material.
[0022] In a preferred embodiment of the present invention, the drying temperature is 50° C. to 200° C., the drying time is 0.5 h to 72 h, and the drying atmosphere is a vacuum atmosphere, an air atmosphere, an argon atmosphere, or a nitrogen atmosphere.
[0023] The second object of the present invention is to provide a block anode for an aluminum electrolytic capacitor prepared by the above-mentioned preparation method.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention prepares a high dielectric constant bulk anode by coating the surface of aluminum powder with a dielectric substance, thereby improving the electrostatic capacitance of the bulk anode. The introduction of the dielectric substance can effectively improve the dielectric constant of the bulk anode, and the dielectric substance is fully diffused after high-temperature heat treatment, thereby improving the electrostatic capacitance. The block integrated molding technology reduces the die-cutting and segmentation process in the manufacturing process of the anode foil, effectively avoiding the generation of burrs and the loss of electrostatic capacitance caused by dead aluminum. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The figure is a schematic diagram of the briquetting mold used in the present invention, wherein a is the briquetting, b is the molding groove, and c is the briquetting molding model.
[0027] Figure 2 This is a simulation diagram of the bulk powder sintering stacked foil obtained in the present invention. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The block anode for aluminum electrolytic capacitors prepared by the present invention makes up for the problem that when the foil anode is die-cut and split, the fresh aluminum exposed needs to be re-formed, which consumes extra energy. The large number of burrs generated by the shearing friction between the metal tool and the foil anode will increase the leakage current after the device is assembled, seriously affecting the service life. It solves the problem that the sintering neck of the powder-stacked sintered anode foil is prone to breakage during winding, resulting in waste of aluminum powder, reduced extraction rate, and loss of electrostatic capacitance. At the same time, the introduction of dielectric material forms a high dielectric constant mixed composite dielectric layer after sintering and energization, which improves the electrostatic capacitance and helps to improve its energy density.
[0030] Mould Figure 1 Shown, including Figure 1 The block shown in a, Figure 1 The molding groove shown in b and Figure 1 In the block forming model shown in c, during the pressing process, a part of the mixed powder is laid in the forming groove for pressing. After the pressing is completed, the block forming model is placed, and the remaining mixed powder is laid and pressed to obtain a block, such as Figure 2 As shown. It can be understood that the blank part of the block forming model is the lead-out piece. It should be noted that the block shaping in the embodiment of the present invention is performed step by step according to this step.
[0031] Aluminum powder has low hardness and is easy to deform. During the pressing process, the aluminum powder on the surface with large force is easy to deform, the inside is loose, and the bulk density is low. During the sintering process, it is easy to cause insufficient decomposition of the binder, and the carbonized organic matter remains in the block. After empowerment, the pores between the powders are blocked by the anodic oxide film, which affects the impregnation of the electrolyte in the later stage, reduces the extraction rate, and further reduces the performance of the device. The present invention effectively alleviates the problem of pore blockage through a step-by-step pressing method. A dielectric coating layer is introduced, and a high dielectric constant mixed composite dielectric layer is formed after sintering and empowerment, which improves the electrostatic capacitance and helps to improve its energy density. In addition, compared with powder-coated foil, the aluminum powder in the powder stacking block is more densely stacked, and the contact between powders is better, which is conducive to the diffusion process during sintering. Therefore, its sintering temperature is lower than that of powder-coated foil.
[0032] The particle diameter of the aluminum powder used in the present invention is 0.5 μm to 30 μm, and its purity is not less than 99.5%. The particle diameter of the dielectric material is 1 nm to 500 nm.
[0033] Example 1
[0034] (1) Aluminum powder with a particle size of 1 μm to 2 μm and a purity of 99.95% and barium titanate with a particle size of 50 nm are uniformly mixed in a mass ratio of 95:5 to obtain dielectric material-coated aluminum powder. In this embodiment, the dielectric material is barium titanate.
[0035] (2) Weigh 65% of dielectric material-coated aluminum powder, 5% of camphor and 30% of anhydrous ethanol according to mass percentage and mix them evenly to obtain a slurry.
[0036] (3) The slurry was dried at 80°C in air atmosphere for 30 min to obtain a mixed powder.
[0037] (4) The mixed powder of step (3) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3 , block thickness 1mm, area 2cm 2 .
[0038] (5) The block obtained in step (4) is degreased in an air atmosphere at 130° C. for 2 h, and sintered in a vacuum atmosphere at 640° C. for 3 h to obtain a sintered block for an aluminum electrolytic capacitor.
[0039] Comparative Example 1
[0040] (1) Weigh 65% aluminum powder, 5% camphor and 30% anhydrous ethanol according to mass percentage and mix them evenly to obtain a slurry. The particle size of the aluminum powder is 1 μm to 2 μm and the purity is 99.95%.
[0041] (2) Drying the slurry in step (1) at 80° C. in an air atmosphere for 30 min to obtain a mixed aluminum powder.
[0042] (3) The mixed aluminum powder of step (2) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3 , block thickness 1mm, area 2cm 2 .
[0043] (4) The block obtained in step (3) was degreased in an air atmosphere at 130° C. for 2 h and sintered in a vacuum atmosphere at 640° C. for 3 h to obtain a block for an aluminum electrolytic capacitor.
[0044] Example 2
[0045] (1) Aluminum powder with a particle size of 4 μm to 5 μm and a purity of 99.95% and barium titanate with a particle size of 50 nm are uniformly mixed in a mass ratio of 95:5 to obtain dielectric material-coated aluminum powder. In this embodiment, the dielectric material is barium titanate.
[0046] (2) Weigh 65% of dielectric material-coated aluminum powder, 5% of camphor and 30% of anhydrous ethanol according to mass percentage and mix them evenly to obtain a slurry.
[0047] (3) The uniformly mixed slurry was dried at 80° C. in air atmosphere for 30 min to obtain a mixed powder.
[0048] (4) The mixed powder of step (3) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3 , block thickness 1mm, area 2cm 2 .
[0049] (5) The block obtained in step (4) was degreased in an air atmosphere at 130° C. for 2 h and sintered in a vacuum atmosphere at 640° C. for 3 h to obtain a block for an aluminum electrolytic capacitor.
[0050] Comparative Example 2
[0051] (1) Weigh 65% aluminum powder, 5% camphor and 30% anhydrous ethanol according to mass percentage to obtain a slurry. The particle size is 4 μm to 5 μm and the purity is 99.95%
[0052] (2) Drying the slurry in step (1) at 80° C. in an air atmosphere for 30 min to obtain a mixed aluminum powder.
[0053] (3) The mixed aluminum powder of step (2) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3 , block thickness 1mm, area 2cm 2 .
[0054] (4) The block obtained in step (3) was degreased in an air atmosphere at 130° C. for 2 h and sintered in a vacuum atmosphere at 640° C. for 3 h to obtain a block for an aluminum electrolytic capacitor.
[0055] Example 3
[0056] (1) Aluminum powder with a particle size of 2 μm to 3 μm and a purity of 99.95% is placed in an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, with nitrogen as the carrier gas and tetraisopropyl titanate (TTIP) as the titanium source. The temperature of the titanium source is maintained at 25°C. The mixture is introduced for 5 seconds, and then nitrogen is introduced for 30 seconds. O3 is then introduced for reaction for 10 seconds, and then nitrogen is introduced for 50 seconds. The above steps are repeated for deposition, and the deposition thickness is 5 nm to obtain dielectric material-coated aluminum powder. In this embodiment, the dielectric material is titanium dioxide.
[0057] (2) Weigh 65% of dielectric material-coated aluminum powder, 5% of camphor and 30% of anhydrous ethanol according to mass percentage and mix them evenly to obtain a slurry.
[0058] (3) The slurry was dried at 80°C in air atmosphere for 30 min to obtain a mixed powder.
[0059] (4) The mixed powder of step (3) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3 , block thickness 1mm, area 2cm 2 .
[0060] (5) The block obtained in step (4) was degreased in an air atmosphere at 130° C. for 2 h and sintered in a vacuum atmosphere at 640° C. for 3 h to obtain a block for an aluminum electrolytic capacitor.
[0061] Example 4
[0062] (1) Aluminum powder with a particle size of 4 μm to 5 μm and a purity of 99.95% is placed in an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, with nitrogen as the carrier gas and TTIP as the titanium source. The temperature of the titanium source is maintained at 25°C, and the mixture is introduced for 5 seconds, followed by nitrogen purge for 30 seconds. Then, O3 is introduced for reaction for 10 seconds, followed by nitrogen purge for 50 seconds. Repeat the above steps to deposit a thickness of 5 nm, and obtain aluminum powder coated with a dielectric material. In this embodiment, the dielectric material is titanium dioxide.
[0063] (2) Weigh 65% of dielectric material-coated aluminum powder, 5% of camphor and 30% of anhydrous ethanol according to mass percentage and mix them evenly to obtain a slurry.
[0064] (3) The slurry was dried at 80°C in air atmosphere for 30 min to obtain a mixed powder.
[0065] (4) The mixed powder of step (3) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3 , block thickness 1mm, area 2cm 2 .
[0066] (5) The block obtained in step (4) was degreased in an air atmosphere at 130° C. for 2 h and sintered in a vacuum atmosphere at 640° C. for 3 h to obtain a block for an aluminum electrolytic capacitor.
[0067] Example 5
[0068] (1) Aluminum powder with a particle size of 2 μm to 3 μm and a purity of 99.95% is coated with titanium dioxide in a sol-gel manner to obtain dielectric material-coated aluminum powder. Specifically, acetylacetone is prepared into an ethanol solution with a concentration of 1.5 mol / L, and then tetrabutyl titanate is added according to a molar ratio of acetylacetone to tetrabutyl titanate of 1:1, stirred for 4 hours, and then 1 / 3 volume of ethanol / water mixed solution in equal proportions is added, stirred for 4 hours, and aluminum powder is added according to a mass ratio of aluminum powder to tetrabutyl titanate of 1:1 and stirred for 1 minute to obtain dielectric material-coated aluminum powder. In this embodiment, the dielectric material is titanium dioxide.
[0069] (2) Weigh 65% of dielectric material-coated aluminum powder, 5% of camphor and 30% of anhydrous ethanol according to mass percentage and mix them evenly to obtain a slurry.
[0070] (3) The uniformly mixed slurry was dried at 80°C in air atmosphere for 30 min to obtain a mixed powder.
[0071] (4) The mixed powder of step (2) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3 , block thickness 1mm, area 2cm 2 .
[0072] (5) The block obtained in step (4) was degreased in an air atmosphere at 430°C for 2 hours and sintered in a vacuum atmosphere at 640°C for 3 hours to obtain a block for an aluminum electrolytic capacitor.
[0073] Example 6
[0074] (1) Aluminum powder with a particle size of 4 μm to 5 μm and a purity of 99.95% is coated with barium titanate in a sol-gel manner to obtain dielectric material coated aluminum powder; titanium dioxide is coated in a sol-gel manner to obtain dielectric material coated aluminum powder. Specifically, acetylacetone is prepared into an ethanol solution with a concentration of 1.5 mol / L, and then tetrabutyl titanate is added according to a molar ratio of acetylacetone to tetrabutyl titanate of 1:1, stirred for 4 hours, and then 1 / 3 volume of ethanol / water mixed solution of equal proportions is added, stirred for 4 hours, and aluminum powder is added according to a mass ratio of aluminum powder to tetrabutyl titanate of 1:1 and stirred for 1 minute to obtain dielectric material coated aluminum powder. In this embodiment, the dielectric material is titanium dioxide.
[0075] (2) Weigh 65% of dielectric material-coated aluminum powder, 5% of camphor and 30% of anhydrous ethanol according to mass percentage and mix them evenly to obtain a slurry.
[0076] (3) The slurry was dried at 80°C in air atmosphere for 30 min to obtain a mixed powder.
[0077] (4) The mixed powder of step (2) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3, block thickness 1mm, area 2cm 2 .
[0078] (5) The block obtained in step (3) was degreased in an air atmosphere at 430°C for 2 hours and sintered in a vacuum atmosphere at 640°C for 3 hours to obtain a block for an aluminum electrolytic capacitor.
[0079] Example 7
[0080] (1) Aluminum powder with a particle size of 4 μm to 5 μm and a purity of 99.95% and niobium oxide with a particle size of 50 nm are uniformly mixed in a mass ratio of 90:10 to obtain aluminum powder coated with a dielectric substance. In this embodiment, the dielectric substance is niobium oxide.
[0081] (2) 40% of dielectric material coated aluminum powder, 0.1% of polyvinyl alcohol and 59.9% of acetonitrile were weighed and mixed uniformly according to mass percentage to obtain a slurry; the molecular weight of the polyvinyl alcohol was 120,000.
[0082] (3) The slurry was dried at 80°C in air atmosphere for 30 min to obtain a mixed powder.
[0083] (4) The mixed powder of step (3) is pressed into a block in a mold to obtain a block having a density of 1.2 g / cm 3 , block thickness 1cm, area 2cm 2 .
[0084] (5) The block obtained in step (4) is degreased in an air atmosphere at 50°C for 10 hours and sintered in a vacuum atmosphere at 250°C for 20 hours to obtain a block for an aluminum electrolytic capacitor.
[0085] Example 8
[0086] (1) Aluminum powder with a particle size of 0.5 μm to 1 μm and a purity of 99.95% and barium titanate with a particle size of 50 nm are uniformly mixed in a mass ratio of 95:5 to obtain dielectric material-coated aluminum powder; in this embodiment, the dielectric material is barium titanate.
[0087] (2) 80% of dielectric material-coated aluminum powder is weighed according to mass percentage, and the dielectric material-coated aluminum powder, 10% of paraffin wax and 10% of methanol are mixed evenly to obtain a slurry.
[0088] (3) The uniformly mixed slurry was dried at 80° C. in air atmosphere for 30 min to obtain a mixed powder.
[0089] (4) The mixed powder of step (3) is pressed into a block in a mold to obtain a block having a density of 2.4 g / cm 3 , block thickness 0.5mm, area 2cm 2 .
[0090] (5) The block obtained in step (4) is degreased in an air atmosphere at 450°C for 0.5 h and sintered in a vacuum atmosphere at 600°C for 0.5 h to obtain a block for an aluminum electrolytic capacitor.
[0091] Example 9
[0092] (1) Aluminum powder with a particle size of 4 μm to 5 μm and a purity of 99.95% and bismuth ferrite with a particle size of 50 nm are uniformly mixed in a mass ratio of 90:10 to obtain dielectric material-coated aluminum powder. In this embodiment, the dielectric material is bismuth ferrite.
[0093] (2) According to the mass percentage, 65% of dielectric material coated aluminum powder, 5% of composite binder and 30% of water are weighed and mixed evenly. The composite binder is composed of starch, polyvinyl alcohol and urea in a mass ratio of 1:1:1, and the molecular weight of polyvinyl alcohol is 120,000.
[0094] (3) The uniformly mixed slurry was dried at 80°C in air atmosphere for 30 min to obtain a mixed powder.
[0095] (4) The mixed powder of step (3) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3 , block thickness 1mm, area 2cm 2 .
[0096] (5) The block obtained in step (4) is degreased in an air atmosphere at 300°C for 2 hours and sintered in a vacuum atmosphere at 450°C for 3 hours to obtain a block for an aluminum electrolytic capacitor.
[0097] Example 10
[0098] (1) Aluminum powder with a particle size of 20 μm to 30 μm and a purity of 99.95% is placed in an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, with nitrogen as the carrier gas and TTIP as the titanium source. The temperature of the titanium source is maintained at 25°C, and the mixture is introduced for 5 seconds, followed by nitrogen purge for 30 seconds. Then, O3 is introduced for reaction for 10 seconds, and then nitrogen purge is introduced for 50 seconds. Repeat the above steps to deposit a thickness of 5 nm to obtain aluminum powder coated with a dielectric material. In this embodiment, the dielectric material is titanium dioxide.
[0099] (2) Weigh 65% of dielectric material coated aluminum powder, 5% of composite adhesive and 30% of pine alcohol according to mass percentage and mix them evenly to obtain a slurry. The composite adhesive is composed of polystyrene, polyvinyl chloride, stearic acid and glycerol in a mass ratio of 1:2:1:1. The molecular weight of polystyrene is 60,000, the molecular weight of polyvinyl chloride is 100,000,
[0100] (3) The slurry was dried at 80°C in air atmosphere for 30 min to obtain a mixed powder.
[0101] (4) The mixed powder of step (3) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3 , block thickness 1mm, area 2cm 2 .
[0102] (5) The block obtained in step (4) was degreased in an air atmosphere at 450°C for 2 hours and sintered in a hydrogen atmosphere at 640°C for 3 hours to obtain a block for an aluminum electrolytic capacitor.
[0103] Embodiment 11
[0104] (1) Aluminum powder with a particle size of 4 μm to 5 μm and a purity of 99.95% and strontium titanate with a particle size of 200 nm are mixed uniformly in a mass ratio of 90:10 to obtain dielectric material-coated aluminum powder. In this embodiment, the dielectric material is strontium titanate.
[0105] (2) Weigh 65% of dielectric material coated aluminum powder, 5% of composite binder and 30% of acetone according to mass percentage and mix them evenly to obtain a slurry. The composite binder is composed of polyethylene oxide, hydroxypropyl cellulose and acrylic resin in a mass ratio of 1:2:2. The molecular weight of polyethylene oxide is 10,000, the molecular weight of hydroxypropyl cellulose is 40,000, and the molecular weight of acrylic resin is 80,000.
[0106] (3) The slurry was dried at 50°C in a nitrogen atmosphere for 72 h to obtain a mixed powder.
[0107] (4) The mixed powder of step (3) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3 , block thickness 1mm, area 2cm 2 .
[0108] (5) The block obtained in step (4) is degreased in an oxygen atmosphere at 400°C for 2 hours and sintered in a vacuum atmosphere at 500°C for 3 hours to obtain a block for an aluminum electrolytic capacitor.
[0109] Example 12
[0110] (1) Aluminum powder with a particle size of 2 μm to 3 μm and a purity of 99.95% is placed in an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, with nitrogen as the carrier gas and hafnium tetradimethylamine as the hafnium source. The temperature of the hafnium source is maintained at 25°C. The mixture is introduced for 5 seconds, and then nitrogen is introduced for 30 seconds. O3 is then introduced for reaction for 10 seconds, and then nitrogen is introduced for 50 seconds. The deposition is repeated according to the above steps, and the deposition thickness is 5 nm to obtain aluminum powder coated with a dielectric material. In this embodiment, the dielectric material is hafnium oxide.
[0111] (2) Weigh 60% of dielectric material coated aluminum powder, 10% of composite binder and 305N,N-dimethylformamide according to mass percentage and mix them evenly to obtain a slurry. The composite binder is composed of polymethyl methacrylate, polypropylene carbonate and polyvinyl butyral in a mass ratio of 1:1:2. Polymethyl methacrylate, polypropylene carbonate and polyvinyl butyral, the molecular weight of polymethyl methacrylate is 100000, the molecular weight of polypropylene carbonate is 280000, and the molecular weight of polyvinyl butyral is 40000.
[0112] (3) The slurry was dried at 80°C in an argon atmosphere for 30 min to obtain a mixed powder.
[0113] (4) The mixed powder of step (3) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3 , block thickness 1mm, area 2cm 2 .
[0114] (5) The block obtained in step (4) is degreased in an air atmosphere at 450°C for 2 hours and sintered in a nitrogen atmosphere at 500°C for 3 hours to obtain a block for an aluminum electrolytic capacitor.
[0115] Example 13
[0116] (1) Aluminum powder with a particle size of 2 μm to 3 μm and a purity of 99.95% is placed in an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, with nitrogen as the carrier gas and Ta(OC2H5)5 as the tantalum source. The tantalum source temperature is maintained at 25°C. The mixture is introduced for 5 seconds, and then nitrogen is introduced for 30 seconds. O3 is then introduced for reaction for 10 seconds, and then nitrogen is introduced for 50 seconds. The deposition is repeated according to the above steps, and the deposition thickness is 5 nm to obtain aluminum powder coated with dielectric material. In this embodiment, the dielectric material is tantalum pentoxide.
[0117] (2) Weigh 60% of dielectric material coated aluminum powder, 10% of menthol and 30% of N-methylpyrrolidone according to mass percentage and mix them evenly to obtain a slurry.
[0118] (3) Dry the slurry at 200°C in an argon atmosphere for 20 min to obtain a mixed powder.
[0119] (4) The mixed powder of step (3) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3 , block thickness 1mm, area 2cm 2 .
[0120] (5) The block obtained in step (4) is degreased in an air atmosphere at 150°C for 2 hours and sintered in an argon atmosphere at 500°C for 3 hours to obtain a block for an aluminum electrolytic capacitor.
[0121] Embodiment 14
[0122] (1) Aluminum powder with a particle size of 4 μm to 5 μm and a purity of 99.95% and barium strontium titanate with a particle size of 1 nm are uniformly mixed in a mass ratio of 90:10 to obtain dielectric material-coated aluminum powder. In this embodiment, the dielectric material is barium strontium titanate.
[0123] (2) 60% of dielectric material coated aluminum powder, 10% of composite binder and 30% of n-butanol were weighed and mixed evenly according to mass percentage to obtain a slurry. The composite binder was composed of benzoic acid and glycerol in a mass ratio of 2:3.
[0124] (3) The slurry was dried at 80°C in air atmosphere for 30 min to obtain a mixed powder.
[0125] (4) The mixed powder of step (3) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3 , block thickness 1mm, area 2cm 2 .
[0126] (5) The block obtained in step (4) was degreased in an air atmosphere at 450°C for 2 hours and sintered in a vacuum atmosphere at 630°C for 3 hours to obtain a block for an aluminum electrolytic capacitor.
[0127] Embodiment 15
[0128] (1) Aluminum powder with a particle size of 4 μm to 5 μm and a purity of 99.95% and lead zirconate titanate with a particle size of 500 nm are uniformly mixed in a mass ratio of 90:10 to obtain dielectric material-coated aluminum powder. In this embodiment, the dielectric material is lead zirconate titanate.
[0129] (2) Weigh 65% of dielectric material coated aluminum powder, 10% of propylene carbonate and 25% of methyl ethyl ketone according to mass percentage and mix them evenly to obtain a slurry.
[0130] (3) Dry the slurry at 200° C. in a vacuum atmosphere for 10 min to obtain a mixed powder.
[0131] (4) The mixed powder of step (3) is pressed into a block in a mold to obtain a block having a density of 1.9 g / cm 3 , block thickness 1mm, area 2cm 2 .
[0132] (5) The block obtained in step (4) is degreased in an air atmosphere at 300°C for 5 hours and sintered in a vacuum atmosphere at 500°C for 3 hours to obtain a block for an aluminum electrolytic capacitor.
[0133] The aluminum capacitor sintered blocks prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 2 were formed in a boric acid system solution according to standard SJ / T11140-2022 at a formation voltage of 500 V or 700 V, and then the electrostatic capacitance was tested in an 80 g / L ammonium pentaborate solution, and the withstand voltage was tested in a 70 g / L boric acid solution. The results are described in Table 1 below.
[0134] Table 1 Test results of withstand voltage and electrostatic capacitance
[0135]
[0136] It can be seen from Table 1 that compared with the electrostatic capacitance and withstand voltage of the pure aluminum powder aluminum block anode in the comparative example, the electrostatic capacitance and withstand voltage of the high dielectric constant aluminum block anode prepared by high dielectric constant coated tantalum powder in Examples 1-6 of the present invention are significantly improved, indicating that the introduction of dielectric material, after high-temperature heat treatment and energization, effectively improves the dielectric constant of the block anode, thereby improving the electrostatic capacitance.
[0137] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0138] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a bulk anode for an aluminum electrolytic capacitor, characterized in that: The following steps are involved: Aluminum powder coated with a dielectric substance, a binder and a solvent are uniformly mixed to obtain a slurry, and the slurry is dried to remove the solvent in the slurry to obtain a mixed powder; the dielectric constant of the dielectric substance is greater than the dielectric constant of aluminum oxide; The mixed powder is pressed and shaped to obtain a block, the block is degreased at 50°C to 450°C in an oxygen-containing atmosphere, sintered at 250°C to 670°C in an oxygen-free atmosphere, and after sintering, an energizing treatment is performed to obtain a block anode for an aluminum electrolytic capacitor.
2. The method for preparing a bulk anode for an aluminum electrolytic capacitor according to claim 1, characterized in that: The dielectric material is one or more of titanium dioxide, hafnium oxide, tantalum pentoxide, niobium oxide, barium titanate, strontium titanate, barium strontium titanate, lead zirconate titanate and bismuth ferrite.
3. The method for preparing a bulk anode for an aluminum electrolytic capacitor according to claim 1, characterized in that: The density of the block is 1.2 g / cm 3 ~2.4g / cm 3 The thickness of the block is 0.5mm~1cm.
4. The method for preparing a bulk anode for an aluminum electrolytic capacitor according to claim 1, characterized in that: The slurry is composed of the following components in percentage by mass: 40% to 80% of aluminum powder coated with dielectric material, 0.1% to 10% of binder, and the rest of solvent, which is 100% in total.
5. The method for preparing a bulk anode for an aluminum electrolytic capacitor according to claim 1, characterized in that: The degreasing time is 0.5h~20h.
6. The method for preparing a bulk anode for an aluminum electrolytic capacitor according to claim 1, characterized in that: The sintering time is 0.5 to 20 hours.
7. The method for preparing a bulk anode for an aluminum electrolytic capacitor according to claim 1, characterized in that: The binder is one or more of starch, polyvinyl alcohol, urea, polymethyl methacrylate, methyl methacrylate, polystyrene, polyvinyl chloride, stearic acid, glycerin, polyethylene glycol, paraffin, camphor, menthol, benzoic acid, polyethylene oxide, hydroxypropyl cellulose, acrylic resin, polypropylene carbonate, polyvinyl butyral and propylene carbonate.
8. The method for preparing a bulk anode for an aluminum electrolytic capacitor according to claim 1, characterized in that: The solvent is water, methanol, ethanol, terpineol, acetonitrile, acetone, N,N-dimethylformamide, N-methylpyrrolidone, n-butanol or methyl ethyl ketone.
9. The method for preparing a bulk anode for an aluminum electrolytic capacitor according to claim 1, characterized in that: The aluminum powder coated with dielectric material is obtained by vapor deposition, liquid coating or solid mixed coating.
10. A block anode for an aluminum electrolytic capacitor prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Nano dielectric powder coated aluminum electrolytic capacitor sintered foil and preparation method thereof
CN115188598A
Electrode foil and preparation method thereof, capacitor and electronic device
CN115376828A
Electrolytic capacitor
GB1307149A
Solid electrolytic capacitor and manufacturing method thereof
JP2008270754A
Cited By
Waste liquid treatment device for production of high-temperature-resistant long-life electrode foil for AI server
CN121554017A
Aluminum powder sintering electrolytic capacitor anode without aluminum foil carrier and preparation method and application thereof
CN122337895A